(NpROZA (B/ s (N~ASTX (B2s - (NbELYJ(B, (NaNDREJs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1990)
(NwO WTOROJ TOM WO[LI PROZAI^ESKIE PROIZWEDENIQ a(B. (NbELOGO(B: "(NpETERBURG(B", "(NkOTIK lETAEW(B", "(NmOSKWA POD UDAROM(B".s
rus
Keywords: (NkLASSI^ESKAQ PROZAs; (NrOMANs